Performance evaluation of Cryo Laser Phoresis technique as biophysical method to promote diclofenac sodium cutaneous perfusion - Marcio Adriano Andréo; Iasmin Mimoto Rufino; Daniela Cecilia Ortiz de Orue Ubaldo; Estela Boaro Herbst; Heron Dominguez Torres da Silva; Pedro Gonçalves de Oliveira; Marcio Ferrari; Paulo Cesar Pires Rosa; Patrícia Santos Lopes; Vânia Rodrigues Leite-Silva
ABSTRACT Aiming to alter and/or improve permeation of active compounds in the skin, many strategies have been developed, including biophysical methods. One of the physical absorption techniques, currently known as Cryo Laser Phoresis (CLP), consists of an apparatus that emits radiation on polar or nonpolar molecules of the active substance, resulting in faster penetration when in comparison to the standard topical application. The goal of this work was to evaluate the efficacy of a method that proposes to increase cutaneous permeation of diclofenac sodium by using CLP technique. The influence on permeation was evaluated ex vivo, using Franz cell and human skin obtained from cosmetic surgery. The results were evaluated using statistical methods and data exploratory analysis: clusters, k-means and Principal Component Analysis. The results showed a larger increase in the concentration of diclofenac sodium in the dermis with the use of laser. In all samples (with or without laser application) it was observed that skin surface showed an amount of diclofenac sodium and that there was no active passage to the receptor liquid, suggesting that diclofenac sodium was not absorbed. These results indicate that CLP, when used under the conditions described in this study, is able to increase diclofenac sodium penetration and its retention into deeper layers.